Деякі особливості біології трипса Liothrips vaneeckei Priesner (Thysanoptera, Phlaeothripidae) та метод знезараження цибулин лілій від нього - Chumak, P.Ya.; Kykot, L.М.; Vygera, S.М. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
The sexual structure of population and the variability of morphological characteristics of lilies dangerous phytophage of thrips Liothrips vaneeckei Priesner are given. An environmentally safe method of bulbs protection from this pest is described.